Flexible hydrogen peroxide detection working electrode based on platinum nanoparticle / laser-induced graphene
By pretreating the hydrophilic site on the polyimide film, and combining laser engraving technology, a platinum nanoparticle/laser induced graphene electrode was prepared, solving the problems of complex preparation, high cost and limited electrode performance in the prior art, and achieving a flexible hydrogen peroxide detection electrode with low cost, high stability and excellent electrode performance.
Patent Information
- Application Number
- CN202411808659.X
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2024-12-10
- Publication Date
- 2025-04-11
AI Technical Summary
The prior art is complex in the preparation of porous graphene electrodes, and the cost is high, and the metal particles are seriously wasted, and the electrode performance optimization is limited.
The preparation method of platinum nanoparticles/laser induced graphene (Pt-LIG) electrode was adopted to pretreat the polyimide film to form hydrophilic sites, and chloroplatinic acid was uniformly deposited, and then the composite structure of the platinum nanoparticles/graphene conductive layer was formed by laser engraving.
A flexible hydrogen peroxide detection working electrode with low cost, high stability and excellent electrode performance is achieved, and the platinum nanoparticles are evenly distributed, avoiding agglomeration and waste.
Smart Images

Figure CN119804586A_ABST
Abstract
Description
Technical Field
[0001] The invention relates to the technical field of flexible sensor production, and in particular to a flexible hydrogen peroxide detection working electrode based on platinum nanoparticles / laser-induced graphene. Background Art
[0002] As an emerging carbon nanomaterial, porous graphene has a series of unique physical and chemical properties such as light weight and high specific surface area. These properties have great application prospects in physics, chemistry, materials science, energy and information science, so its research and exploration have attracted much attention. However, the traditional methods for preparing porous graphene and two-dimensional planar graphene are complicated, and it is difficult to obtain a specific graphic structure with precise graphene. In recent years, laser-induced graphene (LIG) has become a promising technology. It has gradually become an efficient method for graphene manufacturing and can also precisely control the graphic structure.
[0003] Laser-induced graphene (LIG) has an excellent three-dimensional porous structure, a large specific surface area, good high-temperature stability, mechanical properties and biocompatibility. Doping different elements on the surface of LIG to form a composite electrode has been the focus of research in recent years. Taking metal-doped LIG as an example, the existing doping methods are mainly divided into two categories: the first is to mix the corresponding substance with the LIG precursor material in liquid form, dry it to form a solid composite, and then induce it with laser. The second is to directly process LIG, such as electrodeposition.
[0004] The corresponding substances are mixed with the precursor materials of LIG in liquid form, dried to form a solid composite, and then laser induced. The principle is simple but the operation is complicated, and the metal particles formed are not only on the electrode surface, and a large amount of metal particles are wasted, resulting in increased costs. The electrodeposition method is processed after LIG is formed, and the doped elements or substances have problems such as easy agglomeration of particles, uncontrollable morphology, and limited performance optimization. Summary of the invention
[0005] The purpose of the present invention is to provide a flexible hydrogen peroxide detection working electrode based on platinum nanoparticles / laser-induced graphene, which has low cost, stable electrode, good electrode performance and hydrogen peroxide sensitivity.
[0006] The technical solution adopted by the present invention to solve its technical problem is: A flexible hydrogen peroxide detection working electrode based on platinum nanoparticles / laser-induced graphene is prepared by the following method: (1) Pretreatment: The polyimide film is cleaned with anhydrous ethanol, then cleaned with deionized water, and dried; then the polyimide film is placed in a plasma treatment chamber, evacuated to a vacuum degree of 50-80 Pa, and subjected to gas plasma treatment for 80-100 seconds at a power of 150-180 W and carbon dioxide gas; then the polyimide film after plasma treatment is immersed in a potassium hydroxide solution for 25-30 minutes, taken out, and cleaned with deionized water; (2) Soaking in chloroplatinic acid solution: Soak the polyimide film pretreated in step (1) in chloroplatinic acid solution for 3-5 minutes, take it out, and dry it; (3) Laser engraving: The polyimide film treated in step (2) is laser engraved to form a platinum nanoparticle / laser induced graphene electrode.
[0007] The processing method of the electrode of the present invention is different from the traditional electrode processing method. The present invention first processes a large number of uniformly distributed hydrophilic sites on the surface of a polyimide film with low hydrophilicity that cannot load chloroplatinic acid through a pretreatment operation, so that subsequent chloroplatinic acid can be uniformly combined (physically deposited) on the surface of the polyimide film, and then under the action of a laser, while a graphene conductive layer is formed, chloroplatinic acid is converted into platinum nanoparticles and is tightly compounded with the graphene conductive layer, the morphology is controllable, the particles will not agglomerate, the platinum nanoparticles are evenly distributed, and the electrode performance is effectively improved.
[0008] Because polyimide film has weak electrical conductivity, electrodeposition requires matrix to have good electrical conductivity, and it is difficult to realize that graphene electrode can not be processed again by electrodeposition on polyimide film first. Therefore, the present invention adopts specific pretreatment method to polyimide film, first by carbon dioxide plasma etching, etching point can be formed uniformly on polyimide film surface, hydrophilic groups such as carbonyl and carboxyl are introduced simultaneously, the point position after carbon dioxide plasma etching, can guide and locate for potassium hydroxide hydrophilic treatment, further cooperate the hydrophilic treatment of potassium hydroxide, introduce more hydrophilic groups such as hydroxyl, so that hydrophilic binding sites can be formed uniformly on polyimide film surface, so that subsequent chloroplatinic acid can be evenly deposited and distributed on polyimide film surface, and also reduce the waste of platinum. And if chloroplatinic acid is directly coated on polyimide film surface, then because of the water repellency of polyimide film, chloroplatinic acid irregular flow, chloroplatinic acid is not easy to combine and can not be evenly distributed, can have a strong impact on electrode performance.
[0009] Preferably, in step (1), the concentration of the potassium hydroxide solution is 100-110 g / L.
[0010] Preferably, in step (1), the temperature of the potassium hydroxide solution is controlled at 50±1°C.
[0011] Preferably, in step (2), the concentration of the chloroplatinic acid solution is 250-300 mM.
[0012] Preferably, in step (3), the laser engraving machine parameters for laser engraving are set as follows: engraving mode, power 5-5.5 W, scanning rate 250-300 mm / s.
[0013] The invention has the beneficial effects of low processing cost, stable electrode, good electrode performance and hydrogen peroxide sensitivity. BRIEF DESCRIPTION OF THE DRAWINGS
[0014] Figure 1 This is the CV test curve of LIG bare electrode; Figure 2 It is the CV test curve of the LIG electrode with electrodeposited Pt; Figure 3 This is a CV test curve diagram of the Pt-LIG electrode of the present invention; Figure 4 This is the EIS test curve of LIG bare electrode; Figure 5 This is the EIS test curve of the LIG electrode with electrodeposited Pt; Figure 6 This is the EIS test curve of the Pt-LIG electrode of the present invention; Figure 7 is the SEM image of LIG electrode with electrodeposited Pt; Figure 8 is a SEM image of the Pt-LIG electrode of the present invention; Fig. 9 This is the XPS test image of LIG bare electrode; Fig.10 This is the XPS test image of the LIG electrode with electrodeposited Pt; Fig.11 This is the XPS test image of the Pt-LIG electrode of the present invention; Fig.12 is the H2O2 response of the Pt-LIG electrode of the present invention. DETAILED DESCRIPTION
[0015] The technical solution of the present invention is further described in detail below through specific embodiments.
[0016] In the present invention, unless otherwise specified, the raw materials and equipment used can be purchased from the market or are commonly used in the art. The methods in the following embodiments, unless otherwise specified, are all conventional methods in the art.
[0017] Embodiment 1: A flexible hydrogen peroxide detection working electrode based on platinum nanoparticles / laser-induced graphene is prepared by the following method: (1) Pretreatment: A 0.1 mm thick polyimide film (5 cm*5 cm) was cleaned with anhydrous ethanol, then with deionized water, and dried; then the polyimide film was placed in a plasma treatment chamber, evacuated to a vacuum degree of 50 Pa, and subjected to gas plasma treatment for 100 seconds at a power of 150 W and with carbon dioxide gas introduced; then the plasma-treated polyimide film was immersed in a potassium hydroxide solution with a concentration of 100 g / L and a temperature of 50±1°C for 30 min, taken out, and cleaned with deionized water; (2) Soaking in chloroplatinic acid solution: Soak the polyimide film pretreated in step (1) in a 280 mM chloroplatinic acid solution for 5 min, take it out, and dry it; (3) Laser engraving: The polyimide film treated in step (2) is laser engraved to form a platinum nanoparticle / laser-induced graphene electrode. The laser engraving machine parameters for laser engraving are set as follows: engraving mode, power 5W, scanning rate 250mm / s.
[0018] Embodiment 2: A flexible hydrogen peroxide detection working electrode based on platinum nanoparticles / laser-induced graphene is prepared by the following method: (1) Pretreatment: A 0.1 mm thick polyimide film (5 cm*5 cm) was cleaned with anhydrous ethanol, then with deionized water, and dried; then the polyimide film was placed in a plasma treatment chamber, evacuated to a vacuum degree of 80 Pa, and subjected to gas plasma treatment for 80 seconds at a power of 180 W and with the introduction of carbon dioxide gas; then the plasma-treated polyimide film was immersed in a potassium hydroxide solution with a concentration of 110 g / L and a temperature of 50±1°C for 25 min, taken out, and cleaned with deionized water; (2) Soaking in chloroplatinic acid solution: Soak the polyimide film pretreated in step (1) in a 300 mM chloroplatinic acid solution for 3 min, take it out, and dry it; (3) Laser engraving: The polyimide film treated in step (2) is laser engraved to form a platinum nanoparticle / laser-induced graphene electrode. The laser engraving machine parameters for laser engraving are set as follows: engraving mode, power 5.5 W, scanning rate 300 mm / s.
[0019] Embodiment 3: A flexible hydrogen peroxide detection working electrode based on platinum nanoparticles / laser-induced graphene is prepared by the following method: (1) Pretreatment: A 0.1 mm thick polyimide film (5 cm*5 cm) was cleaned with anhydrous ethanol, then with deionized water, and dried; then the polyimide film was placed in a plasma treatment chamber, evacuated to a vacuum degree of 60 Pa, and subjected to gas plasma treatment for 90 seconds at a power of 160 W and with carbon dioxide gas introduced; then the plasma-treated polyimide film was immersed in a potassium hydroxide solution with a concentration of 100 g / L and a temperature of 50±1°C for 30 min, taken out, and cleaned with deionized water; (2) Soaking in chloroplatinic acid solution: Soak the polyimide film pretreated in step (1) in a 250 mM chloroplatinic acid solution for 5 min, take it out, and dry it; (3) Laser engraving: The polyimide film treated in step (2) is laser engraved to form a platinum nanoparticle / laser-induced graphene electrode. The laser engraving machine parameters for laser engraving are set as follows: engraving mode, power 5.1 W, scanning rate 250 mm / s.
[0020] Comparative Example 1: Compared with Example 3, the pretreatment operation in step (1) is eliminated, and the rest is the same as Example 3.
[0021] Comparative Example 2: LIG bare electrode, preparation method: clean a 0.1mm thick polyimide film (5cm*5cm) with anhydrous ethanol, then clean it with deionized water, and dry it; laser engraving: laser engrave the polyimide film to form a laser-induced graphene electrode. The laser engraving machine parameters for laser engraving are: engraving mode, power 5.1W, scanning rate 250mm / s.
[0022] Comparative Example 3: LIG electrode with Pt electrodeposition, preparation method: A 0.1 mm thick polyimide film (5 cm*5 cm) was cleaned with anhydrous ethanol, then cleaned with deionized water, and dried; Laser engraving: The polyimide film was laser engraved to form the LIG electrode. The laser engraving machine parameters for laser engraving were set as follows: engraving mode, power 5.1 W, scanning rate 250 mm / s.
[0023] Then, on an electrochemical workstation, in a 250 mM chloroplatinic acid environment, using a platinum mesh electrode as a counter electrode, an Ag / AgCl electrode as a reference electrode, and a LIG electrode as a working electrode, platinum was electrochemically deposited using a chronoamperometry (IT method) at a voltage of -2 V for 500 s to form a LIG electrode with electro-deposited platinum.
[0024] Electrode performance test: We performed CV and EIS tests on the electrodes. On the electrochemical workstation, a platinum mesh electrode was used as the counter electrode and an Ag / AgCl electrode was used as the reference electrode, and the test was conducted in an environment of 5mM potassium ferrocyanide and 0.1M potassium chloride. The Pt-LIG electrode (the following tests all use Example 3 of the present invention) and the LIG electrode on which Pt was electrodeposited (hereinafter referred to as the electrodeposited LIG electrode) were tested respectively. The CV test results show that the CV peak value of the electrodeposited LIG electrode increased from 0.11mA of the bare electrode to 0.21mA, while the peak value of the Pt-LIG electrode prepared in one step reached 1.6mA ( Figure 1-Figure 3 ), which greatly improves the redox capacity of the electrode.
[0025] EIS impedance test also gave similar results. R ct The values are 1200Ω, 775Ω and 135Ω respectively ( Figure 4-Figure 6 ). The two sets of tests together show that the Pt-LIG electrode greatly optimizes the conductivity of the LIG bare electrode, and the effect is much better than the traditional electrodeposition Pt method.
[0026] The present invention significantly reduces the agglomeration of platinum nanoparticles: To explain the optimization of electrode performance, we first observed the morphology of platinum nanoparticles using a scanning electron microscope (SEM). Figure 7-8 By comparison, it can be observed that compared with traditional electrodeposition platinum plating (electrodeposition LIG), Pt-LIG not only retains the porous structure of graphene, but also allows platinum nanoparticles to be relatively evenly doped on the graphene surface, overcoming the problems of platinum nanoparticles clumping and particles being too large, which block the graphene pores in traditional methods.
[0027] In addition, we also conducted XPS tests and focused on the C1s peak. The C1s peak mainly reflects the content of CC bonds on the electrode surface, while the other peaks represent possible defects. Figure 9-11 It can be seen that the attachment of platinum nanoparticles does not change the basic structure of the CC bond, but based on Fig.10 It can be judged that the electrodeposition method causes more surface CC bonds to be covered, which is not conducive to electron transfer.
[0028] The present invention has a better hydrogen peroxide response: In most applications, Pt is mainly used to catalyze the decomposition of hydrogen peroxide. Therefore, the sensitivity to hydrogen peroxide is an important indicator for evaluating the electrode. We use the chronoamperometry (IT method) to monitor the electrode's response to hydrogen peroxide in a 0.01Mpbs solution environment, and select 0.55V as the applied voltage to minimize the interference of electroactive substances. Fig.12 As shown, the sensitivity of the electrode to hydrogen peroxide is about 6.95 μA / mM (R 2=0.934). In terms of response time, the response current can reach 50% of the equilibrium potential 10s after adding H2O2, indicating that it has excellent H2O2 sensitivity.
[0029] We compared the corresponding electrode performance with and without pretreatment. For Example 1, which was not pretreated, the corresponding water contact angle (reflecting the hydrophilicity) was 13.2°, the corresponding water contact angle for Example 3 was 5.4°, the corresponding water contact angle for Example 2 was 7.6°, and the corresponding water contact angle for Example 2 was 6.5°. There are also obvious differences in their impedance: the electrode impedance of Example 1 is greater than 600 ohms, while the electrode impedance of Example 3 is about 135 ohms. In addition, there are also large differences in hydrogen peroxide response: the sensitivity of Example 1 is about 2.85μA / mM, and the sensitivity of Example 3 is about 6.95μA / mM.
[0030] The above-described embodiment is only a preferred solution of the present invention and does not limit the present invention in any form. There are other variations and modifications without exceeding the technical solution described in the claims.
Claims
1. A flexible hydrogen peroxide detection working electrode based on platinum nanoparticles / laser-induced graphene, characterized in that: Prepared by the following method: (1) Pretreatment: The polyimide film is cleaned with anhydrous ethanol, then cleaned with deionized water, and dried; then the polyimide film is placed in a plasma treatment chamber, evacuated to a vacuum degree of 50-80 Pa, and subjected to gas plasma treatment for 80-100 seconds at a power of 150-180 W and carbon dioxide gas; then the polyimide film after plasma treatment is immersed in a potassium hydroxide solution for 25-30 minutes, taken out, and cleaned with deionized water; (2) Soaking in chloroplatinic acid solution: Soak the polyimide film pretreated in step (1) in chloroplatinic acid solution for 3-5 minutes, take it out, and dry it; (3) Laser engraving: The polyimide film treated in step (2) is laser engraved to form a platinum nanoparticle / laser induced graphene electrode.
2. The flexible hydrogen peroxide detection working electrode based on platinum nanoparticles / laser induced graphene according to claim 1, characterized in that: In step (1), the concentration of the potassium hydroxide solution is 100-110 g / L.
3. The flexible hydrogen peroxide detection working electrode based on platinum nanoparticles / laser induced graphene according to claim 1 or 2, characterized in that: In step (1), the temperature of the potassium hydroxide solution is controlled at 50±1°C.
4. The flexible hydrogen peroxide detection working electrode based on platinum nanoparticles / laser induced graphene according to claim 1, characterized in that: In step (2), the concentration of the chloroplatinic acid solution is 250-300 mM.
5. The flexible hydrogen peroxide detection working electrode based on platinum nanoparticles / laser induced graphene according to claim 1, characterized in that: In step (3), the laser engraving machine parameters for laser engraving are set as follows: engraving mode, power 5-5.5 W, and scanning rate 250-300 mm / s.